On design of multi-cell thin-wall structures for crashworthiness - Wu, Suzhen; Zheng, Gang; Sun, Guangyong; Liu, Qiang; Li, Guangyao; Li, Qing (International journal of impact engineering, 2016)
•Establish finite element modeling of five-cell tube and conduct experimental validation.•Divulge the evolution rule of the number of cells and the topological configurations of multi-cell structures.•Conduct parameter analysis for five-cell tube under dynamic impact.•Perform optimization design for five-cell tube under dynamic impact. Multi-cell thin-wall structures have drawn increasing attention and been widely applied in automotive and aerospace industries for their significant advantages in high energy absorption and lightweight. The number of cells and the topological configurations of the multi-cell thin-wall structures have a significant effect on the crashworthiness. In order to investigate the effect of the number of cells and the topological configurations of multi-cell structures on their crashworthiness characteristics, this paper first sets up the simulation models of multi-cell tubes and verifies their accuracy with the quasi-static and dynamic impact experiments. Second, it compares the energy absorption characteristics of the multi-cell structures with different numbers of cells and topological configurations under dynamic impact condition using finite element analysis (FEA). The results show that the mean crushing force (MFC) and specific energy absorption (SEA) increase with the increase in the number of cells of the multi-cell tubes, among which the five-cell tube has the best energy absorption characteristics. Third, a parametric study is carried out to investigate the effects of wall thickness and topology configurations on the crashworthiness of five-cell tubes. Finally, the multiobjective Non-dominated Sorting Genetic Algorithm (NSGA-II) is used to further optimize the five-cell tube for maximizing specific energy absorption and minimizing peak crushing force (PCF). The optimal five-cell tube has excellent crashworthiness and is a potential energy absorber.